PENERAPAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) DALAM PERANCANGAN APLIKASI PEMILIHAN PASANGAN BERBASIS WEB - Chrisantus Robert William Resi; Yusuf Kurnia; Hartana Wijaya; Dera Susilawati (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2021)
As social beings, humans have a desire to socialize, to build deeper relationships with individuals they like, and also to get a spouse according to the criteria they like. However, there are often obstacles in finding a spouse, one of which is due to being too busy and an increasing workload. Luckily we live in an era of technology that makes it easier for us to interact with other people. The spouse selection application itself is quite common for several circles in Indonesia, but some of these applications are considered not fully providing services to recommend a spouse based on the criteria. Therefore, it is necessary to design an application that helps users find a spouse according to the criteria they like. In this application, the Simple Additive Weighting (SAW) method will be used to process data. The SAW method itself has the ability to find optimal alternatives from a number of alternatives with certain criteria.